IMPLEMENTASI STRATEGI POSE UNTUK MEMBERDAYAKAN CRITICAL THINKING MAHASISWA STKIP PGRI BLITAR - Suryanti Suryanti; Cicik Pramesti (Universitas Islam Malang, 2015)
Background of the problem is that students are unable to predict and organize structures in Aljabar Structure I subject which is used as a tool to show a statement. The purpose of this research is to describe the implementation of POSE strategy(Predict, Organize, Summarize and Evaluate) which can empower critical thinking to students of mathematic education program of STKIP PGRI Blitar in Aljabar Structure I subject. The research uses qualitative approach with research design of Eliot model class action. The result based on the final test in the classical cycle 89,5% of the 19 students who take the test are in the category of critical potency good or excellent. The average percentage of final observation for lecturer and students activities in every meeting is catagorized good and excellent. The result of critical thinking activity sheet (LACT) in every meeting is in category good critical potency or critical potency. The result conclude that the implementation of POSE strategy which can empower critical thinking to students of mathematic education programme in subject of Structure Aljabar